THE INFLUENCE OF READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) LEARNING ON COGNITIVE ABILITIES AND COMMUNICATION SKILLS - Hanbali, Ayala Paska; Isrokatun, I; Ismail, Ali (Journal Of Educational Experts (JEE), 2024)
This research was motivated by the low cognitive abilities and communication skills of students. This research aims to determine the effect of RADEC learning on students' cognitive abilities and communication skills. The approach taken in this research was quantitative with a quasi-experimental method and a non-equivalent control group design. The population in this study was 34 State Elementary Schools in North Sumedang District. Sampling used a purposive sampling technique, so that the research sample was selected, namely SDN Tegalkalong. The instruments in this research consisted of test and non-test instruments. Test questions are used to measure students' cognitive abilities which have been tested for validity and reliability. The non-test instrument is an observation sheet to observe students' communication skills during RADEC learning. The research results show that RADEC learning has a positive influence on students' cognitive abilities and communication skills. It is proven from the test results that the average difference in questions measuring cognitive abilities and the posttest results are higher than the pretest results. After implementing RADEC learning, students' communication skills become more active, especially when expressing opinions and using language that is easy to understand. Therefore, RADEC learning can be used to improve students' cognitive abilities and communication skills.